O mundo se despedaça: anticolonialismo, literatura e ensino de história da África - Soares, Michele Barbosa (2023)
This work is part of the line of research on Historical Languages and Narratives: Production and Dissemination and also The teaching of African History and aims to explore the didacticuses of the book Things Falls Apart by the nigerian writer Chinua Ach ebe in the teaching of History, focusing on the experiences of colonization and decolonization on the African continent in order to build paths and strategies for teaching the history of Africa that enables the construction of knowledge and positive unders tanding of African populations in dialogue with the parameters established by (brazilian) law 10.639/2003 and the National Curriculum Guidelines for Education of Ethnic and Racial Relations for the teaching of African and Afro Brazilian History and Culture , that is, perceiving them as protagonists of the historical processes and not in a stereotyped way. For this purpose, a theoretical dialogue with anticolonial studies is established, which allowed us to reflect and elaborate a didactic sequence aimed at teaching African history.